Mapping a Bounded Scopus Corpus on STEAM-Related Learning Processes: A Bibliometric Analysis (2015–2026) - Qamariah Qamariah; Misbah Misbah; Ismail Ismail; Muhdi Harto; Surya Haryandi; Erwina Oktavianty (Gawi: Journal of Action Research, 2026)
This study maps the development and thematic structure of a bounded Scopus corpus on STEAM-related learning processes through bibliometric analysis. Data were retrieved from the Scopus database on March 26, 2026, using a predefined TITLE-ABS-KEY search strategy restricted to English-language journal articles in the final publication stage. The final corpus consisted of 115 documents published between 2015 and 2026. The analysis combined performance indicators and author-keyword co-occurrence analysis to examine publication growth, leading countries, affiliations, sources, productive authors, influential documents, and thematic structures within the retrieved corpus. The results show that publication output increased substantially after 2020 and reached its highest level in 2025, while the 2026 count remained provisional, as it reflected a partial publication year. The United States emerged as the leading contributor, whereas the International University of La Rioja and Universitas Negeri Jakarta were the most productive affiliations. Computer Applications in Engineering Education was the most productive source. Document-level citation analysis showed that teacher professional development, educational robotics, challenge-based learning, computational thinking, project-based learning, and technology-enhanced learning environments constitute influential foundations of the corpus. Author-keyword co-occurrence analysis identified thematic concentrations related to multilingual pedagogical practices, teacher knowledge, teacher professional development, inclusive science education, digital pedagogy, literacy development, and educational equity. These findings indicate that the retrieved corpus is characterized less by broad STEAM research in general and more by pedagogical, teacher-capacity, literacy, and learning-process-oriented issues. This study contributes a transparent bibliometric profile of a bounded Scopus corpus and demonstrates how retrieval logic influences thematic structures in bibliometric mapping.